Microplastics in Taihu Lake, China. (September 2016) - Su, Lei; Xue, Yingang; Li, Lingyun; Yang, Dongqi; Kolandhasamy, Prabhu; Li, Daoji; Shi, Huahong
Abstract: In comparison with marine environments, the occurrence of microplastics in freshwater environments is less understood. In the present study, we investigated microplastic pollution levels during 2015 in Taihu Lake, the third largest Chinese lake located in one of the most developed areas of China. The abundance of microplastics reached 0.01 × 10 6 –6.8 × 10 6 items/km 2 in plankton net samples, 3.4–25.8 items/L in surface water, 11.0–234.6 items/kg dw in sediments and 0.2–12.5 items/g ww in Asian clams ( Corbicula fluminea ). The average abundance of microplastics was the highest in plankton net samples from the southeast area of the lake and in the sediments from the northwest area of the lake. The northwest area of the lake was the most heavily contaminated area of the lake, as indicated by chlorophyll-α and total phosphorus. The microplastics were dominated by fiber, 100–1000 μm in size and cellophane in composition. To our best knowledge, the microplastic levels measured in plankton net samples collected from Taihu Lake were the highest found in freshwater lakes worldwide. The ratio of the microplastics in clams to each sediment sample ranged from 38 to 3810 and was negatively correlated to the microplastic level in sediments. In brief, our results strongly suggest that high levels of microplastics occurred not only in water but also in organisms in Taihu Lake. Graphical abstract: Highlights: Microplastic reached 0.01 × 10 6 –6.8 × 10 6 items/km 2 in plankton net samples in Taihu Lake. There were 3.4–25.8 items/L in surface water and 11.0–234.6 items/kg dw in sediments. Microplastic distribution in plankton net samples was different from that in sediments. Uptake of microplastics in clams was negatively correlated to microplastics in sediments. Relative high levels of microplastics were found in Taihu Lake. Abstract : High levels of microplastics occurred not only in water but also organisms (Asian clams) in Taihu Lake, China.